Systematic material and crack type specific pipe burst outflow simulations by means of EPANET2. Issue 2 (17th February 2016) - Fuchs-Hanusch, D.; Steffelbauer, D.; Günther, M.; Muschalla, D.
Abstract : The calculation of outflow from pipe bursts is of interest for water utilities, as the discharged water may cause large amounts of damage to the adjacent infrastructure. Therefore, the crack type specific relationship between leakage outflow and pressure is of interest. Recent findings offer new opportunities for burst outflow calculations with hydraulic models. In this paper, we compare two calculation approaches according to uncertainties caused by input parameters and give recommendations for the applicability of the methods. Simulations in a case study area have shown large leakage outflow differences between the two approaches for longitudinal cracks. For circumferential cracks, the differences are smaller. Further, due to the uncertain leak size and form of probable bursts we involved Monte Carlo simulations in the model approach. These allow the derivation of mean values and standard deviations of leakage outflow per pipe section to make the uncertainty of the results more transparent.